Insulating coating solution for oriented silicon steel, preparation method and insulating coating
By proportioning aluminum dihydrogen phosphate, aluminum oxalate, silica sol, potassium fluorozirconate, yttrium oxide and 1,4-butanediol in the insulating coating solution, an excellent insulating, corrosion-resistant and heat-resistant insulating coating is formed, and poor insulating properties, corrosion-resistant, heat-resistant, adhesion and environmentally friendly motor coatings are solved in the prior art, and a high-efficiency, long-life and environmentally friendly motor coating is achieved.
Patent Information
- Application Number
- CN202510069945.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-16
AI Technical Summary
The existing oriented silicon steel insulating coating technology has poor insulation, corrosion resistance, heat resistance, adhesion and environmental protection performance, and cannot meet the needs of new energy vehicle motors for high efficiency, long life and environmental protection.
An insulating coating solution is adopted, which consists of aluminum dihydrogen phosphate solution, aluminum oxalate, silica sol, potassium fluorozirconate, yttrium oxide and 1,4-butanediol. Through specific ratios and preparation methods, an insulating coating with excellent insulation, corrosion resistance, heat resistance and adhesion are formed.
It significantly improves the insulation, corrosion resistance and heat resistance of oriented silicon steel, forms a uniform, dense and environmentally friendly coating, extends the service life of the motor, improves working efficiency, and meets environmental protection requirements.
Smart Images

Figure BDA0005245412540000071 
Figure BDA0005245412540000091 
Figure BDA0005245412540000101
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of silicon steel insulating coating preparation, and in particular to an insulating coating solution, a preparation method and an insulating coating for oriented silicon steel. Background Art
[0002] The rapid development of new energy vehicles, especially pure electric vehicles, has put forward higher requirements on the performance of motors, especially in terms of efficiency, life and energy saving. The performance of motors directly affects the competitiveness of the whole vehicle, and the stator core and rotor core, which are the core components of the motor, are mainly made of oriented silicon steel. The insulation, corrosion resistance and heat resistance of oriented silicon steel have an important impact on the efficiency and life of the motor. However, the surface coating of traditional oriented silicon steel generally uses a coating containing hexavalent chromium. Although it has certain insulation and corrosion resistance, the use of hexavalent chromium causes serious harm to the environment and human health.
[0003] To solve the above problems, current research focuses on the development of chromium-free and environmentally friendly insulating coatings. There are many chromium-free coating technologies, but they have shortcomings such as rough coating surface, poor adhesion or unstable insulation performance. In addition, the uniformity and heat resistance of chromium-free coatings during high-temperature processing still need to be further optimized. In summary, the existing insulating coating technologies have poor insulation, corrosion resistance, heat resistance, adhesion and environmental protection performance, and cannot meet the use requirements. Summary of the invention
[0004] An insulating coating solution, a preparation method and an insulating coating for oriented silicon steel provided in an embodiment of the present invention at least solve the problems of poor insulation, corrosion resistance, heat resistance, adhesion and environmental protection performance of the insulating coating technology in the related art.
[0005] According to a first aspect of an embodiment of the present invention, an insulating coating solution for oriented silicon steel is provided. Based on the total mass of the insulating coating solution, the composition and corresponding mass percentages of the insulating coating solution are: 20% to 25% of aluminum dihydrogen phosphate solution, 4% to 6% of aluminum oxalate, 30% to 35% of silica sol, 3% to 5% of potassium fluorozirconate, 1% to 2% of yttrium oxide, 2% to 3% of 1,4-butanediol and the remainder of water.
[0006] According to an embodiment of the present invention, the aluminum dihydrogen phosphate solution is an aluminum dihydrogen phosphate aqueous solution, and the mass percentage of aluminum dihydrogen phosphate in the aluminum dihydrogen phosphate aqueous solution is 50%.
[0007] According to an embodiment of the present invention, the aluminum oxalate is aluminum oxalate dodecahydrate, and the solid content of the aluminum oxalate dodecahydrate is greater than 99%.
[0008] According to an embodiment of the present invention, the average particle size of the silica sol is 5-8 nm, the mass percentage of SiO2 in the silica sol is 20-21%, the pH value is 10-11, and the viscosity is 2.0-2.5 MPa·s.
[0009] According to an embodiment of the present invention, the potassium fluorozirconate is white crystals with a solid content of more than 99%.
[0010] According to an embodiment of the present invention, the yttrium oxide is in the form of powder, and the solid content thereof is greater than 99.5%.
[0011] According to an embodiment of the present invention, the 1,4-butanediol is liquid, and its mass percentage is more than 99%.
[0012] According to a second aspect of an embodiment of the present invention, a method for preparing an insulating coating solution is provided, wherein the raw materials of the insulating coating solution include, by mass percentage, 20% to 25% of aluminum dihydrogen phosphate solution, 4% to 6% of aluminum oxalate, 30% to 35% of silica sol, 3% to 5% of potassium fluorozirconate, 1% to 2% of yttrium oxide, 2% to 3% of 1,4-butanediol, and the remainder of water, the method comprising:
[0013] Add the aluminum oxalate and the potassium fluorozirconate into water and stir;
[0014] After the aluminum oxalate and the potassium fluorozirconate are completely dissolved, the aluminum dihydrogen phosphate solution is added and stirred;
[0015] After the aluminum dihydrogen phosphate solution is fully mixed, the yttrium oxide is added while stirring;
[0016] After the yttrium oxide is completely dissolved, the silica sol and the 1,4-butanediol are added and stirred until the mixture is uniform to obtain a mixed solution;
[0017] The mixed solution is filtered through a 1250-mesh filter to obtain the insulating coating solution.
[0018] According to a third aspect of an embodiment of the present invention, an insulating coating for oriented silicon steel is provided, wherein the insulating coating is obtained by coating oriented silicon steel with the insulating coating solution according to the first aspect.
[0019] According to an embodiment of the present invention, the insulating coating solution according to the first aspect is used to coat the oriented silicon steel, and the coating is then heated, dried, and sintered to eventually form an insulating coating on the surface of the oriented steel.
[0020] Beneficial effects of the embodiments of the present invention:
[0021] The embodiment of the present invention significantly improves the insulation performance, corrosion resistance and heat resistance of oriented silicon steel by proportioning aluminum oxalate, potassium fluorozirconate, yttrium oxide and other components in the phosphate coating solution. The addition of aluminum oxalate effectively reduces the conductivity of silicon steel and significantly enhances the resistivity of the insulating coating; potassium fluorozirconate, as an environmentally friendly substitute, not only completely eliminates the pollution problem of chromium-containing compounds to the environment and health, but also makes the coating have excellent corrosion resistance; the addition of yttrium oxide improves the stability of the coating in a high temperature environment, reduces the iron loss caused by thermal expansion during the processing of silicon steel, and thus improves the magnetic properties. After coating, baking and high-temperature sintering on the surface of oriented silicon steel, the insulating coating solution of the embodiment of the present invention forms a layer of environmentally friendly coating with excellent insulation, adhesion, corrosion resistance and heat resistance, and the coating is uniform and dense. The oriented silicon steel sheet coated with the coating is used to manufacture the stator core and rotor core of the tram motor, which not only improves the working efficiency and service life of the motor, but also achieves energy-saving effects, provides reliable technical support for the efficient operation of the tram motor, and meets environmental protection requirements at the same time, and has important industrial value and application prospects. DETAILED DESCRIPTION
[0022] The embodiments of the present embodiment will be described in more detail below. Although certain embodiments of the present embodiment are described, it should be understood that the present embodiment can be implemented in various forms and should not be interpreted as being limited to the embodiments set forth herein, which are instead provided to provide a more thorough and complete understanding of the present embodiment. It should be understood that the content of the present embodiment is only for exemplary purposes and is not intended to limit the scope of protection of the present embodiment.
[0023] An embodiment of the present invention provides an insulating coating solution for oriented silicon steel and a preparation method thereof, wherein the composition and proportion of the insulating coating solution are designed to ensure the excellent performance of the coating in terms of high temperature, corrosion resistance, adhesion and insulation performance.
[0024] The insulating coating solution for oriented silicon steel of the embodiment of the present invention, based on the total mass of the insulating coating solution, has main components and corresponding mass percentage ranges as follows: 20% to 25% of aluminum dihydrogen phosphate solution, 4% to 6% of aluminum oxalate, 30% to 35% of silica sol, 3% to 5% of potassium fluorozirconate, 1% to 2% of yttrium oxide, 2% to 3% of 1,4-butanediol and the balance of water. The specific functions of each component and the basis for its selection will be described one by one below.
[0025] In this embodiment, the aluminum dihydrogen phosphate solution is an aluminum dihydrogen phosphate aqueous solution, and the mass percentage of aluminum dihydrogen phosphate in the aluminum dihydrogen phosphate aqueous solution is 50%.
[0026] The role of aluminum dihydrogen phosphate in this embodiment is to provide film-forming properties and improve the adhesion of the coating. Its unique chemical properties enable it to form a strong bond with the base material. By selecting a 50% mass percent concentration of aluminum dihydrogen phosphate solution, it can be ensured that aluminum dihydrogen phosphate can fully exert its film-forming and adhesion effects, and at the same time, there is enough aluminum dihydrogen phosphate to participate in the formation of a solid structure during the coating curing process, thereby improving the mechanical strength and electrical insulation properties of the coating. A concentration of 50% can effectively react with other ingredients in the subsequent mixing process, and it is not easy to be overly diluted or concentrated, thereby ensuring the stability and effect of the coating solution.
[0027] Specifically, aluminum dihydrogen phosphate, as the main film-forming component of the coating solution of the present invention, has good high temperature resistance, peeling resistance and insulation performance. The aluminum ions in aluminum dihydrogen phosphate form a strong binding force with the coating surface, and its small atomic radius can promote the close bonding between the coating and the substrate, ensuring that the coating is not easy to peel off during use, and has good insulation after curing. Its mass percentage accounts for 20% to 25% of the total mass of the coating solution, which can provide sufficient film formation and adhesion to ensure that the coating is stable and durable.
[0028] In an optional embodiment, when preparing the aluminum dihydrogen phosphate solution, first, prepare a solid raw material of aluminum dihydrogen phosphate and deionized water. Take an appropriate amount of aluminum dihydrogen phosphate powder and accurately weigh it to ensure that the mass percentage content of aluminum dihydrogen phosphate in the final solution is 50%. Then, add deionized water to a stirring container and slowly add aluminum dihydrogen phosphate powder. To ensure complete dissolution, the mixture can be gently stirred with the help of a stirrer until the aluminum dihydrogen phosphate is completely dissolved to form a clear and transparent solution.
[0029] During the dissolution process, the stirring speed can be adjusted to make the dissolution rate of aluminum dihydrogen phosphate in water uniform and stable. If the solution temperature is found to rise too quickly, the stirring speed needs to be appropriately reduced, and the temperature of the solution can be controlled by cooling the water bath to prevent excessive reaction of certain components in the solution due to excessive temperature.
[0030] Furthermore, to ensure that the concentration of aluminum dihydrogen phosphate solution reaches 50%, the final solution concentration can be confirmed by comparing the actual dissolved aluminum dihydrogen phosphate mass and solution volume. If the concentration is insufficient, aluminum dihydrogen phosphate powder can be added in an appropriate amount and stirring can be continued until the solution concentration meets the requirements.
[0031] Ultimately, the prepared aluminum dihydrogen phosphate solution should have uniform concentration and stability, and can be used as an important component in the coating solution to play its role in film formation and adhesion enhancement in the subsequent coating preparation process.
[0032] In this embodiment, the aluminum oxalate is aluminum oxalate dodecahydrate, and the solid content of the aluminum oxalate dodecahydrate is greater than 99%.
[0033] Aluminum oxalate dodecahydrate (solid content ≥ 99%) is selected as the raw material to ensure its high purity and few impurities, so that it can react stably and fully play its role in the preparation process. High-purity aluminum oxalate can effectively reduce the impact of impurities on the performance of the coating, ensuring that the final coating has good adhesion, high temperature resistance and corrosion resistance.
[0034] Specifically, aluminum oxalate plays two important roles in the coating solution: on the one hand, it can remove dirt attached to the surface of silicon steel and improve the coating performance of the coating solution; on the other hand, aluminum oxalate can also complex the metal impurity ions on the surface of silicon steel, react with the metal impurities during high-temperature baking to form an oxide film, further improving the insulation performance of the coating. The mass percentage of aluminum oxalate accounts for 4% to 6% of the total mass of the coating solution, which can effectively enhance the bonding force between the coating and the substrate and improve the adhesion and durability of the coating.
[0035] In this embodiment, the average particle size of the silica sol is 5-8 nm, the mass percentage of SiO2 in the silica sol is 20-21%, the pH value is 10-11, and the viscosity is 2.0-2.5 MPa·s.
[0036] Silica sol is an important component in the coating solution. As an auxiliary film-forming substance, silica sol plays an important role in the adhesion, surface smoothness and heat resistance of the coating. Its smaller particle size (5-8nm) can improve the density of the coating and reduce the formation of micropores, thereby improving the mechanical strength and electrical insulation performance of the coating. The mass percentage of SiO2 is 20-21%, which can provide sufficient film-forming substances to ensure uniform and stable coating.
[0037] At the same time, the pH value and viscosity of silica sol are also crucial to the quality of the coating. A pH value of 10-11 is conducive to enhancing the stability of silica sol and promoting its compounding with other components. A viscosity of 2.0-2.5 MPa·s ensures that the coating has appropriate fluidity and wettability, making it easy to apply to the surface of silicon steel and form a uniform coating.
[0038] Specifically, silica sol, as an auxiliary film-forming agent, plays an important role in enhancing adhesion and improving surface quality in the coating solution. The addition of silica sol can not only improve the adhesion of the coating, but also compound with the phosphate binder to prevent the shrinkage and bubbling of the single phosphate coating during high-temperature baking, avoid the formation of micropores, and improve the smoothness and uniformity of the coating. The average particle size of silica sol is 5-8nm, the mass percentage content of SiO2 is 20-21%, the pH value is 10-11, and the viscosity is 2.0-2.5MPa·s. Its dosage accounts for 30%-35% of the total mass of the coating solution, ensuring the excellent adhesion and surface quality of the coating.
[0039] In an optional embodiment, the silica sol in the embodiment of the present invention can be prepared in the following manner. First, prepare an appropriate amount of silicon tetrachloride and deionized water. Pour deionized water into a stirring container and slowly add silicon tetrachloride under stirring. Silicon tetrachloride rapidly undergoes hydrolysis reaction in water to generate silica gel and release hydrogen chloride gas. To control the reaction rate, ammonia water can be slowly added during the reaction to adjust the pH value of the solution so that it is maintained between about 10 and 11. By adjusting the amount of ammonia water added, the particle size distribution of the silica sol can be accurately controlled. After the reaction continues for a period of time, the generated silica sol will be filtered to remove impurities therein, and concentrated by ultrafiltration and other methods to obtain the desired silica sol solution. Finally, the particle size of the silica sol can be further controlled by adjusting the reaction conditions (such as temperature, pH value, ammonia water addition rate, etc.) to ensure that the particle size is between 5 and 8nm. After purification and adjustment, a silica sol that meets the requirements of the present invention is finally obtained, with a mass percentage content of SiO2 of 20-21%, and having the required viscosity and stability.
[0040] The silica sol prepared by this method has a uniform particle size distribution, which can meet the requirements of the coating solution for silica sol particle size, concentration and stability, and can ensure that the final coating has excellent adhesion, smoothness and thermal stability.
[0041] In this embodiment, potassium fluorozirconate is white crystals with a solid content of more than 99%.
[0042] Potassium fluorozirconate is an important component in the coating solution and is mainly used to improve the corrosion resistance of the coating and enhance the impact resistance of the coating. In the embodiment of the present invention, potassium fluorozirconate replaces the traditional chromium-containing compounds, avoiding the potential harm of chromium compounds to the environment, and at the same time meets environmental protection requirements while ensuring the performance of the coating.
[0043] Potassium fluorozirconate with a solid content of more than 99% is selected as the raw material to ensure its stability and high efficiency in the coating solution. High-purity potassium fluorozirconate can reduce the interference of impurities on the coating performance and ensure the corrosion resistance and mechanical strength of the coating.
[0044] Specifically, potassium fluorozirconate, as an environmentally friendly material, replaces traditional chromium-containing compounds, which not only effectively improves the corrosion resistance of the coating, but also improves the punching performance of the coating, preventing the coating from being damaged during the punching and lamination of silicon steel sheets. This characteristic makes the coating more stable during the manufacturing process while maintaining its excellent electrical insulation properties. The mass percentage of potassium fluorozirconate accounts for 3% to 5% of the total mass of the coating solution, ensuring the stability of the coating during the punching and lamination process while meeting environmental protection requirements.
[0045] In this embodiment, yttrium oxide is in powder form, and the solid content is above 99.5%.
[0046] Yttrium oxide has excellent heat resistance due to its high melting point and boiling point, and can significantly improve the high temperature resistance of the coating. In high temperature environments, yttrium oxide can reduce the thermal expansion of the coating and reduce the damage to the coating caused by thermal stress, thereby improving the stability and durability of the coating. In addition, the addition of yttrium oxide can also improve the magnetic properties and electrical insulation properties of the coating, which is particularly important in the application of oriented silicon steel.
[0047] Selecting yttrium oxide powder with a solid content of more than 99.5% as raw material can ensure its high purity and reduce the influence of other impurities, thereby improving the overall performance and stability of the coating. High-purity yttrium oxide can provide better thermal stability and enhance the high temperature resistance of the coating.
[0048] Specifically, yttrium oxide can significantly improve the high temperature resistance of the coating due to its high melting point and boiling point. After adding yttrium oxide, the coating can maintain good stability after high-temperature baking and is suitable for applications in high temperature environments. Yttrium oxide has a small thermal expansion coefficient at high temperatures, which means that the coating will not break due to thermal expansion during thermal cycling, which helps to reduce thermal stress between the coating and the substrate, reduce iron loss and improve magnetic properties. The mass percentage of yttrium oxide accounts for 1% to 2% of the total mass of the coating solution, which provides a guarantee for stability and long life in high-temperature applications.
[0049] In this embodiment, 1,4-butanediol is liquid, and its mass percentage is more than 99%.
[0050] The role of 1,4-butanediol in the coating solution is to reduce the viscosity of the coating solution and improve the wettability of the coating solution, so that the coating solution can be evenly coated on the surface of the silicon steel to form a flat and smooth coating. After the coating solution is baked at high temperature, the coating surface is smooth, the appearance quality is improved, and the coating thickness is uniform, and it is not easy to produce bubbles or uneven coating.
[0051] Selecting liquid 1,4-butanediol with a mass percentage content of more than 99% ensures that it is fully dissolved and effective in the coating solution. High-purity 1,4-butanediol helps to obtain better coating effects and ensure the uniformity and appearance quality of the coating.
[0052] Specifically, 1,4-butanediol as a plasticizer can reduce the viscosity of the coating liquid and increase the wettability of the coating liquid, so that the coating liquid can be evenly coated on the surface of the silicon steel to avoid uneven coating. After high-temperature baking, the coating liquid can form an insulating coating with a smooth surface and improve the appearance quality of the coating. The mass percentage of 1,4-butanediol accounts for 2% to 3% of the total mass of the coating solution, which can effectively improve the coating properties of the coating liquid and the appearance of the coating.
[0053] Another embodiment of the present invention provides a method for preparing an insulating coating solution. The raw materials of the insulating coating solution in this embodiment include, by mass percentage, 20% to 25% of aluminum dihydrogen phosphate solution, 4% to 6% of aluminum oxalate, 30% to 35% of silica sol, 3% to 5% of potassium fluorozirconate, 1% to 2% of yttrium oxide, 2% to 3% of 1,4-butanediol, and the balance of water. The method includes:
[0054] Step S101, adding aluminum oxalate and potassium fluorozirconate into water and stirring.
[0055] In this embodiment, aluminum oxalate and potassium fluorozirconate are first added to water and stirred. Aluminum oxalate is generally aluminum oxalate dodecahydrate, which releases aluminum ions after dissolution, which helps the adhesion and structural strength of the coating. Potassium fluorozirconate can enhance the thermal stability and corrosion resistance of the coating as an additive. By stirring, it can be ensured that aluminum oxalate and potassium fluorozirconate are completely dissolved in water, providing a uniform solution basis for subsequent steps.
[0056] Step S102, after the aluminum oxalate and potassium fluorozirconate are completely dissolved, add the aluminum dihydrogen phosphate solution and stir.
[0057] In this embodiment, after aluminum oxalate and potassium fluorozirconate are completely dissolved, aluminum dihydrogen phosphate solution is added. Aluminum dihydrogen phosphate solution is an aqueous solution containing aluminum dihydrogen phosphate, which provides an aluminum source and helps improve the high temperature resistance and insulation properties of the coating. By stirring, it can be ensured that aluminum dihydrogen phosphate can be fully mixed in the solution to avoid precipitation or uneven distribution.
[0058] Step S103, after the aluminum dihydrogen phosphate solution is fully mixed, yttrium oxide is added while stirring.
[0059] In this embodiment, yttrium oxide is added after the aluminum dihydrogen phosphate solution is fully mixed with other components. Yttrium oxide is a high temperature stable material that can enhance the thermal stability and corrosion resistance of the coating. After addition, stirring needs to be continued to ensure that the yttrium oxide is completely dissolved or evenly dispersed. By adding and stirring, the yttrium oxide can be fully dissolved or dispersed in the solution to form a stable mixed solution.
[0060] Step S104, after the yttrium oxide is completely dissolved, add silica sol and 1,4-butanediol and stir until the mixture is uniform to obtain a mixed solution.
[0061] In this embodiment, the solution obtained after the yttrium oxide is completely dissolved is stirred and mixed with silica sol and 1,4-butanediol to obtain a mixed solution. The SiO2 particles in the silica sol can provide insulation properties and enhance the structural stability of the coating. 1,4-butanediol, as a plasticizer, can improve the fluidity and uniformity of the coating and ensure that the coating forms a consistent film on the metal surface.
[0062] Step S105, filtering the mixed solution through a 1250-mesh filter to obtain an insulating coating solution.
[0063] In this embodiment, the solution is filtered through a 1250 mesh filter to remove any possible solid impurities, ensure the purity and uniformity of the coating solution, and finally obtain a clear coating solution without particulate impurities, ensuring the quality and uniformity of the coating.
[0064] Another embodiment of the present invention provides an insulating coating for oriented silicon steel, which can be obtained by coating oriented silicon steel with the insulating coating solution in the above embodiment.
[0065] In this embodiment, the insulating coating solution in the above embodiment is used to coat the oriented silicon steel, and the coating is then heated, dried, and sintered to eventually form an insulating coating on the surface of the oriented steel.
[0066] In practical applications, the thickness of the insulating coating for oriented silicon steel provided in the embodiment of the present invention may be 0.5-1 μm.
[0067] Before further describing the specific embodiments of the present invention, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terms used in the examples of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods in the following examples without specifying specific conditions are generally carried out under conventional conditions or under conditions recommended by the manufacturers.
[0068] When the embodiments give numerical ranges, it should be understood that, unless otherwise specified in the present invention, both endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those generally understood by those skilled in the art. In addition to the specific methods, equipment, and materials used in the embodiments, according to the grasp of the prior art by those skilled in the art and the record of the present invention, any methods, equipment, and materials of the prior art similar or equivalent to the methods, equipment, and materials described in the embodiments of the present invention can also be used to realize the present invention.
[0069] Example 1
[0070] The oriented silicon steel is coated with an environmentally friendly insulating coating solution prepared according to the formula shown in Table 1. After the coating, the temperature is increased at 50°C / s, dried at 300°C for 30s, and then sintered at 800°C for 30 seconds. Finally, an insulating coating of 0.5 to 1 μm can be formed on the surface of the oriented silicon steel.
[0071] The specific preparation steps are as follows: add potassium fluorozirconate solid, aluminum oxalate solid, and deionized water into a stirring container, and stir thoroughly until the solid is completely dissolved; add aluminum dihydrogen phosphate solution into the above solution and stir evenly, then add yttrium oxide powder, stirring while adding until it is completely dissolved. Mix the solution obtained by the above two steps with silica sol and 1,4-butanediol, stir evenly; filter with a 1250 mesh filter to finally obtain an environmentally friendly insulating coating solution coated on the surface of oriented silicon steel for manufacturing electric motors for electric vehicles.
[0072] The formula of each component is shown in Table 1 (the balance is deionized water):
[0073] Table 1 Composition of coating solution ingredients
[0074]
[0075]
[0076] Note: The balance is deionized water (mass percentage).
[0077] The mass percentage of the aluminum dihydrogen phosphate solution used in Examples 1 to 10 is 50%.
[0078] The aluminum oxalate used in Examples 1 to 10 is dodecahydrate, and its solid content is 99.5%.
[0079] The average particle size of the silica sol used in Examples 1 to 10 is 6 nm, the mass percentage of SiO2 in the silica sol is 20.5%, the pH value is 10.5, and the viscosity is 2.2 MPa·s.
[0080] The potassium fluorozirconate used in Examples 1 to 10 is white crystals with a solid content of 99.2%.
[0081] The yttrium oxide used in Examples 1 to 10 is in powder form, and its solid content is 99.9%.
[0082] The 1,4-butanediol used in Examples 1 to 10 is liquid, and its mass percentage content is 99.5%.
[0083] The aluminum dihydrogen phosphate solution, aluminum oxalate, silica sol, potassium fluorozirconate, yttrium oxide, and 1,4-butanediol used in Comparative Examples 1 to 10 and Examples 1 to 10 are all from the same batch of raw materials.
[0084] Table 2 shows the various properties of the environmentally friendly insulating coating prepared according to the formula and method of Table 1; the oriented silicon steel sheets coated with the insulating coating are punched and stacked to form the motor stator core and rotor core, and the performance of the tram motor assembled using the stator core, rotor core and windings.
[0085] Coating: Appearance is determined by SEM (scanning electron microscope), gloss meter, and roughness measuring instrument.
[0086] The insulation is measured by an insulation resistance tester (by evaluating the interlayer resistance). When the interlayer resistance is >30Ω·(cm2·sheet)-1, the insulation is excellent. When the interlayer resistance is between 15 and 30Ω·(cm2·sheet)-1, the insulation is good. When the interlayer resistance is between 5 and 15Ω·(cm2·sheet)-1, the insulation is fair. When the interlayer resistance is <5Ω·(cm2·sheet)-1, the insulation is poor.
[0087] Adhesion: According to the method specified in GB2522-2007 "Test method for adhesion of insulation resistance coating on surface of electrical steel sheet (strip)", the sample is bent 180° with a diameter of 30mm to check the cracking and peeling of the surface coating.
[0088] The corrosion resistance test is carried out in a circulating corrosion box. Corrosion conditions: spray with 5% saline solution for 5 hours at 35°C, and observe the surface of the sample after taking it out. The corrosion resistance evaluation standard is: rust area <5% is excellent, rust area 5% to 29% is good, rust area 30% to 59% is fair, and rust area >60% is poor.
[0089] The heat resistance test is carried out in a high-temperature box-type resistance furnace. Heat resistance conditions: N2 is introduced at 850℃, and the sample surface is observed after continuous heating for 2 hours. The heat resistance evaluation criteria are: dark gray with gloss is excellent; gray with gloss is good; gray with no gloss is fair; white surface and powdery is poor.
[0090] Motor: The insulation resistance is measured with a 500V megohmmeter. Connect the two leads of the megohmmeter to any two phases to obtain the insulation resistance value of the phase. The insulation resistance value of the motor should be greater than 1 megohm. If the measured insulation resistance value is less than 1 megohm, it means that the insulation performance of the motor is poor, which may cause problems such as motor leakage, short circuit, overheating, etc. The motor with good insulation performance has a relatively long service life and relatively high working efficiency.
[0091] The efficiency is measured indirectly. First, the input power of the motor is measured: by measuring the current and voltage of the motor, the input power of the motor is calculated using the power formula P=UI; then the output power of the motor is measured: by measuring the load torque (T) and speed (ω) of the motor, the output power of the motor is calculated using the power formula P=Tω; finally, the output power of the motor is divided by the input power and multiplied by 100% to get the working efficiency of the motor.
[0092] The temperature rise test uses the thermal balance method. After the motor is run for 2 hours at an ambient temperature of 25°C, an infrared thermometer is used to measure the temperature of each part of the motor. The measured temperature minus the ambient temperature is the temperature rise of the motor. The standard for the motor temperature rise is between 60 and 80°C, which is a relatively safe range that can ensure that the motor will not be damaged due to excessive temperature during normal operation. If the motor temperature rise is too high, it will accelerate the aging of the motor insulation, affect the service life of the motor, and even cause accidents such as motor burnout.
[0093] Table 2 Performance comparison
[0094]
[0095]
[0096] It can be seen from Table 2 that under the conditions of Examples 1 to 10, the coating properties such as appearance, insulation, adhesion, corrosion resistance and heat resistance are all excellent; the oriented silicon steel sheets coated with the environmentally friendly insulating coating are punched and stacked to form motor stator cores and rotor cores, and the tram motors assembled using the stator cores, rotor cores and windings have good insulation performance, high working efficiency, low temperature rise level and long service life.
[0097] Compared with Example 1, the addition of aluminum oxalate in Comparative Example 1 can significantly improve the insulation of the coating. The electric vehicle motor assembled using the oriented silicon steel sheets coated with the insulating coating containing aluminum oxalate has good insulation performance, high working efficiency, and the temperature rise is within a safe range.
[0098] Comparison Example 2 shows that when the content of aluminum oxalate is increased to more than 6%, the performance of the coating and the motor is not significantly improved. It can be seen from the examples that when the addition amount of aluminum oxalate is between 4% and 6%, the performance of the coating and the motor is excellent.
[0099] Compared with Example 3, due to insufficient addition of silica sol, there are a few pinhole-like holes on the surface of the coating, and the insulation, adhesion and corrosion resistance of the coating are reduced. The insulation and working efficiency of the tram motor assembled using the oriented silicon steel sheets coated with this coating are reduced.
[0100] Compared with Example 4, the amount of silica sol added in Comparative Example 4 is too high, resulting in a slightly rough coating surface, a small amount of small particles precipitated, a decrease in the insulation and heat resistance of the coating, insufficient insulation performance of the assembled motor, significantly reduced work efficiency, and a temperature rise beyond the safe range. It can be seen from the examples that the amount of silica sol added is between 30% and 35%, and the coating and the motor have excellent performance.
[0101] Compared with Example 5, the addition of potassium fluorozirconate in Comparative Example 5 can make the coating have excellent corrosion resistance, and can also improve the insulation and heat resistance of the coating, thereby improving the insulation performance and working efficiency of the electric vehicle motor.
[0102] Compared with Example 6, Comparative Example 6 shows that the performance of the coating and the motor has not been significantly improved with the increase of potassium fluorozirconate content. It can be seen from the examples that the performance of the coating and the motor is excellent when the addition amount of potassium fluorozirconate is between 3% and 5%.
[0103] Compared with Example 7, the addition of yttrium oxide in Comparative Example 7 significantly improves the heat resistance of the coating and improves the insulation of the coating. The insulation performance of the tram motor assembled using oriented silicon steel sheets coated with an insulating coating without yttrium oxide is insufficient, the working efficiency is significantly reduced, and the temperature rise is too high.
[0104] Compared with Example 8, Comparative Example 8 shows that the performance of the coating and the motor has not been improved with the increase of yttrium oxide content. It can be seen from the examples that the performance of the coating and the motor is excellent when the addition amount of yttrium oxide is between 1% and 2%.
[0105] Compared with Example 9, if 1,4-butanediol is not added to the coating liquid, its wettability is insufficient, the insulating coating formed on the surface of the silicon steel after high-temperature baking is slightly rough and has white patterns, and the insulation, adhesion, corrosion resistance and heat resistance of the coating are reduced. The insulation performance and working efficiency of the tram motor assembled with the oriented silicon steel sheets coated with the insulating coating without adding 1,4-butanediol are significantly reduced, and the temperature rise exceeds the safe range.
[0106] Compared with Example 10, Comparative Example 10 shows that the performance of the coating and the motor has not been significantly improved with the increase of the 1,4-butanediol content. It can be seen from the examples that when the addition amount of 1,4-butanediol is between 2% and 3%, the performance of the coating and the motor is excellent.
[0107] The present invention implements the coating liquid by using a roller coater to coat the cold-rolled oriented silicon steel substrate, and after coating, the temperature is raised at 50°C / s, dried at 300°C for 30s, and then sintered at 800°C for 30s, and finally an insulating coating of 0.5 to 1 μm can be formed on the surface of the oriented silicon steel.
[0108] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of patent protection. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the scope of protection of the present invention. Therefore, the scope of protection of the present invention shall be subject to the attached claims.
Claims
1. An insulating coating solution for oriented silicon steel, characterized in that: Based on the total mass of the insulating coating solution, the composition and corresponding mass percentages of the insulating coating solution are: 20% to 25% of aluminum dihydrogen phosphate solution, 4% to 6% of aluminum oxalate, 30% to 35% of silica sol, 3% to 5% of potassium fluorozirconate, 1% to 2% of yttrium oxide, 2% to 3% of 1,4-butanediol and the balance of water.
2. The insulating coating solution according to claim 1, characterized in that: The aluminum dihydrogen phosphate solution is an aluminum dihydrogen phosphate aqueous solution, and the mass percentage of aluminum dihydrogen phosphate in the aluminum dihydrogen phosphate aqueous solution is 50%.
3. The insulating coating solution according to claim 1, characterized in that: The aluminum oxalate is aluminum oxalate dodecahydrate, and the solid content of the aluminum oxalate dodecahydrate is greater than 99%.
4. The insulating coating solution according to claim 1, characterized in that: The average particle size of the silica sol is 5-8 nm, the mass percentage of SiO2 in the silica sol is 20-21%, the pH value is 10-11, and the viscosity is 2.0-2.5 MPa·s.
5. The insulating coating solution according to claim 1, characterized in that: The potassium fluorozirconate is a white crystal with a solid content of more than 99%.
6. The insulating coating solution according to claim 1, characterized in that: The yttrium oxide is in powder form, and the solid content is above 99.5%.
7. The insulating coating solution according to claim 1, characterized in that: The 1,4-butanediol is liquid, and its mass percentage is more than 99%.
8. A method for preparing an insulating coating solution, characterized in that: The raw materials of the insulating coating solution include, by mass percentage concentration, 20% to 25% of aluminum dihydrogen phosphate solution, 4% to 6% of aluminum oxalate, 30% to 35% of silica sol, 3% to 5% of potassium fluorozirconate, 1% to 2% of yttrium oxide, 2% to 3% of 1,4-butanediol, and the balance of water. The method includes: Add the aluminum oxalate and the potassium fluorozirconate into water and stir; After the aluminum oxalate and the potassium fluorozirconate are completely dissolved, the aluminum dihydrogen phosphate solution is added and stirred; After the aluminum dihydrogen phosphate solution is fully mixed, the yttrium oxide is added while stirring; After the yttrium oxide is completely dissolved, the silica sol and the 1,4-butanediol are added and stirred until the mixture is uniform to obtain a mixed solution; The mixed solution is filtered through a 1250-mesh filter to obtain the insulating coating solution.
9. An insulating coating for oriented silicon steel, wherein: The insulating coating is obtained by coating oriented silicon steel with the insulating coating solution according to any one of claims 1 to 7.
10. The insulating coating according to claim 9, characterized in that: The oriented silicon steel is coated with the insulating coating solution according to any one of claims 1 to 7, and the coating is then heated, dried, and sintered to finally form an insulating coating on the surface of the oriented steel.
Citation Information
Patent Citations
Treating agent for use in formation of chromium-free insulating coating film, and oriented electromagnetic steel sheet having insulating coating film attached thereto and method for manufacturing same
CN112771203A
Preparation method of inorganic insulating wear-resistant coating
CN116285436A
Zirconate insulating environment-friendly coating for cold-rolled non-oriented electrical steel as well as preparation method and application of zirconate insulating environment-friendly coating
CN117887291A
Process for forming an adherent insulating coating on a sheet of magnetic steel
FR2672305A1
Surface treating agent containing no chromium and grain oriented magnetic steel sheet using the same
JP2000178760A